Mitochondrial Role in Stemness and Differentiation of Hematopoietic Stem Cells - Luena Papa; Mansour Djedaini; Ronald Hoffman (Stem Cells International)
Quiescent and self-renewing hematopoietic stem cells (HSCs) rely on glycolysis rather than on mitochondrial oxidative phosphorylation (OxPHOS) for energy production. HSC reliance on glycolysis is considered an adaptation to the hypoxic environment of the bone marrow (BM) and reflects the low energetic demands of HSCs. Metabolic rewiring from glycolysis to mitochondrial-based energy generation accompanies HSC differentiation and lineage commitment. Recent evidence, however, highlights that alterations in mitochondrial metabolism and activity are not simply passive consequences but active drivers of HSC fate decisions. Modulation of mitochondrial activity and metabolism is therefore critical for maintaining the self-renewal potential of primitive HSCs and might be beneficial for ex vivo expansion of transplantable HSCs. In this review, we emphasize recent advances in the emerging role of mitochondria in hematopoiesis, cellular reprograming, and HSC fate decisions.